Bordetella pertussis entry into respiratory epithelial cells and intracellular survival - Lamberti, Yanina Andrea (2013)
Bordetella pertussis is the causative agent of pertussis, aka whooping cough. Although generally considered an extracellular pathogen, this bacterium has been found inside respiratory epithelial cells, which might represent a survival strategy inside the host. Relatively little is known, however, about the mechanism of internalization and the fate of B. pertussis inside the epithelia. We show here that B. pertussis is able to enter those cells by a mechanism dependent on microtubule assembly, lipid raft integrity, and the activation of a tyrosine-kinase-mediated signaling. Once inside the cell, a significant proportion of the intracellular bacteria evade phagolysosomal fusion and remain viable in nonacidic lysosome-associated membrane-protein-1-negative compartments. In addition, intracellular B. pertussis was found able to repopulate the extracellular environment after complete elimination of the extracellular bacteria with polymyxin B. Taken together, these data suggest that B. pertussis is able to survive within respiratory epithelial cells and by this means potentially contribute to host immune system evasion.